NMDA Receptor Antagonism in the Lateral/Basolateral but Not Central Nucleus of the Amygdala Prevents the Induction of Facilitated Learning in Response to Stress - Shors, Tracey J. (Cold Spring Harbor Laboratory Press, 1998)
Exposure to an acute stressful event facilitates classical eye-blink conditioning in the male rat. The facilitation persists for days after the stressor and its induction is prevented by antagonism of the N-methyl-d-aspartate (NMDA) type of glutamate receptor. To determine whether NMDA receptor antagonists prevent the facilitated conditioning by activity in the amygdala, a competitive antagonist, AP5, was injected bilaterally into the lateral/basolateral versus central nuclei of the amygdala. Local injection of d,l-2-amino-5-phosphonovaleric acid (AP5) into the lateral/basolateral nucleus before stressor exposure prevented the facilitated learning 24 hr later, whereas antagonism in the central nucleus before stressor exposure did not. To determine when the necessary activation occurs, AP5 was injected into the lateral/basolateral nucleus before versus after exposure to the acute stressful event. Blockade of NMDA receptors before but not after stressor exposure prevented the facilitated acquisition of the conditioning in response to stress. These results suggest that exposure to a stressful event transiently activates NMDA receptors in basolateral/lateral nuclei of the amygdala and thereby induces a persistent enhancement of associative learning.